Identifying the Reasons for Software Project Failure and Some of their Proposed Remedial through BRIDGE Process Models - Mandal, Ardhendu; Pal, SC (International Journal of Computer Sciences and Engineering, 2015)
There are enough evidences of software project failures. Starting from economic losses to live losses is caused by many software project failures. Software project failures have significant impact on both social and economic factors. Hence, it is important to identify the different reasons for project failures. If these reasons are pre-known, actions can be taken during project development to reduce project failure risks. In this paper we identify and categorized the project failure root causes based on their different sources. Then briefly we have highlighted the primary features of the BRIDGE [1] process model and explored the ways and means how these project failure reasons may be reduced or alleviated by following the BRIDGE process model.